Visual saliency estimation through label propagation. Issue 14 (1st July 2015) - Tian, Xiaoliang; Jung, Cheolkon
Abstract : Visual saliency estimation through label propagation is proposed. Since salient regions are generally distinctive from the background, visual saliency is estimated in an image by the similarity to salient and non‐salient seeds. First, salient and non‐salient seeds from the initial saliency map estimated by superpixel segmentation and three common priors are obtained. Then, labels of seeds are propagated to unlabelled superpixels based on label propagation to obtain the visual saliency map. Experimental results demonstrate that the proposed method is very effective in estimating salient regions in images compared with existing state‐of‐the‐art methods.